ANG II and Aldosterone Acting Centrally Participate in the Enhanced Sodium Intake in Water-Deprived Renovascular Hypertensive Rats - Gabriela Maria Lucera; José Vanderlei Menani; Eduardo Colombari; Débora Simões Almeida Colombari (Frontiers Media S.A., 2021)
Renovascular hypertension is a type of secondary hypertension caused by renal artery stenosis, leading to an increase in the renin-angiotensin-aldosterone system (RAAS). Two-kidney, 1-clip (2K1C) is a model of renovascular hypertension in which rats have an increased sodium intake induced by water deprivation (WD), a common situation found in the nature. In addition, a high-sodium diet in 2K1C rats induces glomerular lesion. Therefore, the purpose of this study was to investigate whether angiotensin II (ANG II) and/or aldosterone participates in the increased sodium intake in 2K1C rats under WD. In addition, we also verified if central AT1 and mineralocorticoid receptor blockade would change the high levels of arterial pressure in water-replete (WR) and WD 2K1C rats, because blood pressure changes can facilitate or inhibit water and sodium intake. Finally, possible central areas activated during WD or WD followed by partial rehydration (PR) in 2K1C rats were also investigated. Male Holtzman rats (150-180 g) received a silver clip around the left renal artery to induce renovascular hypertension. Six weeks after renal surgery, a stainless-steel cannula was implanted in the lateral ventricle, followed by 5-7 days of recovery before starting tests. Losartan (AT1 receptor antagonist) injected intracerebroventricularly attenuated water intake during the thirst test. Either icv losartan or RU28318 (mineralocorticoid receptor antagonist) reduced 0.3 M NaCl intake, whereas the combination of losartan and RU28318 icv totally blocked 0.3 M NaCl intake induced by WD in 2K1C rats. Losartan and RU28318 icv did not change hypertension levels of normohydrated 2K1C rats, but reduced the increase in mean arterial pressure (MAP) produced by WD. c-Fos expression increased in the lamina terminalis and in the NTS in WD condition, and increased even more after WD-PR. These results suggest the participation of ANG II and aldosterone acting centrally in the enhanced sodium intake in WD 2K1C rats, and not in the maintenance of hypertension in satiated and fluid-replete 2K1C rats.